2018
DOI: 10.1097/qad.0000000000001795
|View full text |Cite
|
Sign up to set email alerts
|

Multitype violence exposures and adolescent antiretroviral nonadherence in South Africa

Abstract: Objectives:HIV-positive adolescents have low-ART adherence, with consequent increased risks of mortality, morbidity, and viral resistance. Despite high rates of violence against children in the Africa region, no known studies have tested impacts on HIV-positive adolescents. We examine associations of ART adherence with adolescent violence victimization by caregivers, teachers, peers, community members, and healthcare providers.Design and methods:HIV-positive adolescents were interviewed (n = 1060), and clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 60 publications
1
35
1
Order By: Relevance
“…However, similarities also emerged. These resonated with findings from quantitative and qualitative datasets of the Mzantsi Wakho study, including the enduring effects of HIV-related stigma, and the impacts of various socio-structural determinants on adherence to ART (Cluver et al, 2016(Cluver et al, , 2018Toska et al, 2016;. Findings 'Yummy of Crummy?'…”
Section: Mzantsi Wakho: Study Context and Designmentioning
confidence: 83%
See 2 more Smart Citations
“…However, similarities also emerged. These resonated with findings from quantitative and qualitative datasets of the Mzantsi Wakho study, including the enduring effects of HIV-related stigma, and the impacts of various socio-structural determinants on adherence to ART (Cluver et al, 2016(Cluver et al, , 2018Toska et al, 2016;. Findings 'Yummy of Crummy?'…”
Section: Mzantsi Wakho: Study Context and Designmentioning
confidence: 83%
“…The disclosure of their HIV-status, by a nurse or family member, was often accompanied by new understandings about the illness and death of their parents and siblings. Within the quantitative sample, an estimated 75% of adolescents were perinatally infected, and 59% had lost one or both parents (Cluver et al, 2018).…”
Section: Mzantsi Wakho: Study Context and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For many, taking ART inconsistently was an experience that was difficult to convey, particularly since admissions of non-adherence were often followed by reproaches or reprimands by guardians and health providers, who viewed it as their duty to oversee, coax, and at times enforce adherence. Responses to caregivers' and healthcare workers' discoveries of non-adherence among adolescents ranged from verbal rebukes to physical threats and punishments, and took place both in homes and in clinics (Cluver et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies-for example, in Tanzania [18], South Africa [19,20], and Malawi [21]have assessed exposure to violence among HIV-positive youth as an independent or adjustment variable, reporting wide-ranging prevalence figures derived from widely varying measures and methodologies. Only one study was identified for which violence was the primary focus in a population of HIV-positive adolescents in SSA; this study by Cluver et al found that between 41% and 47% of the sample of 1,060 South African boys and girls (ages [10][11][12][13][14][15][16][17][18][19] reported exposure to past-year physical or verbal violence from teachers, peers, or community members [22] but did not measure IPV. While there is limited data on HIV-positive adolescents (up to age 19), there is virtually no information available on HIV-positive young men (aged 20-24 years) and violence victimization in SSA.…”
Section: Introductionmentioning
confidence: 99%